“GUESS GEOMETRY”: MEDIA PENUNJANG APERSEPSI KONSEP KESEBANGUNAN DAN KEKONGRUENAN BANGUN DATAR - Doni Setya Darmawan; Galih Setiawan; Nazalia Rahma; Devi Dwi Jayanti; Husnul Khotimah; Lailatul Fitria (TRANSFORMASI, 2026)
The long time span between materials makes it possible for students to forget the concepts of two-dimensional shapes. Therefore, a method is needed to remind students, one of which is by using game media. The purpose of this study was to apply the “Guess Geometry” media in the apperception process of the concept of quadrilaterals and triangles as a basis for learning the concept of similarity and congruence. The subjects were six seventh-grade students at one of the Islamic Junior High Schools in Banyuwangi with high abilities. This study used qualitative methods. Data collection was carried out using observation, interviews, and documentation methods. The researcher acted as the main instrument and was assisted by observation and interview guidelines. Data were analyzed qualitatively using the Miles & Huberman model. The study resulted in 3 subjects winning according to the indicator by guessing 3 to 5 two-dimensional shapes correctly in less than 30 minutes. The other 3 subjects showed misconceptions about the properties of similar two-dimensional shapes. Nevertheless, the media can be used to support the apperception process of the concept of similarity and congruence with teacher guidance, especially for students with low and medium abilities.